PELATIHAN MENANAM HIDROPONIK DALAM UPAYA KETAHANAN PANGAN DI DESA NGEJENG BOJONEGORO - Ari Kuntardina; Nurrahma Luckysyah; Widya Septiani Shofyanna; Maulida Rohmatul Laeliya; Neli Agustina; Delia Kholifatul Mala; Rima Fatmawati; Rizal Aryanto; Anita Firdous Alifia (Buletin Abdi Masyarakat, 2021)
The impact of the Covid-19 pandemic affected most of the people of Ngrejeng village, Purwosari District, Bojonegoro Regency. Some people have been temporarily dismissed and some have even lost their jobs. The aim of this program is to empower the community by providing training in farming with a hydroponic system. The concept of "Hydroponics" is a way of planting using nutritious mineral solutions without using soil by emphasizing the nutritional needs of plants. The long-term output expected from this program is the improvement of food security and community welfare through hydroponics. Community service activities are carried out in the following stages: (1) presentation of "Hydroponics"; (2) training and practice of hydroponic farming for the community; and (3) assistance for three months on hydroponic gardening practices. The result of this program is the formation of hydroponic gardens which are placed in RT 08 / RW 02 Ngrejeng village which are managed jointly, as well as hydroponic gardens planted by five groups of residents. Keywords: Hidroponic, Farming, Empowering Community, Food Security.